Isolamento dos principais constituintes de natureza terpênica e avaliação das atividades biológicas de Senecio selloi Spreng DC. - Silva, Gloria Narjara Santos da (2010)
Species belonging to the genus Senecio contain metabolites with potential biological activities, as flavonoids and terpenoids. This work involves the chemical and biological analysis of Senecio selloi Spreng DC. (Asteraceae), popularly known as catião-melado, which grows as a shrub in southern Brazil. The plant material was collected in Guaíba, RS, in April 1998 and November 2004 and 2006. After the extraction of the aerial parts using different methods, the TLC analysis was carried out and the antimicrobial activity of the ethanolic extract, its fractions, the essential oil, the isolated compounds, as well as the dichloromethanic and ethanolic extracts of the roots was performed using microdilution broth method. For the ethanolic extract and fractions of the aerial parts, the best result was obtained for the hexanic (MIC and MBC 78 g/mL) and ethyl acetate (MIC 310 g/mL and MBC 630 g/mL) fractions against Klebsiella pneumoniae. The extraction of essential oil was performed by hydrodistillation. Its constituents were identified by comparison of Kovats indices and mass spectra with literature data. After analysis by GC/MS, nineteen compounds were identified, representing 99.9% of the oil. The major constituents were: -zingiberene (54%), isolimonene (16%), para-Mentha- 3,8-diene (5,7%), germacrene D (4,4%), caryophyllene (4,1%) and -curcumene (4,1%). The essential oils presented antimicrobial activity only against Bacillus subtilis (MIC and MBC 4.400 μg/mL). The dichloromethanic extract of the roots showed the best result against Staphylococcus aureus ATCC 25923 (MIC and MBC of 2.500 μg/mL). The crude ethanolic extract and fractions were assessed for the production of thiobarbituric acid reactive species (TBARS) and determination of the phenolic content by the method of Folin- Ciocalteau. The ethyl acetate fraction showed the highest antioxidant potential and the highest phenolic concentration (2662.1 nmol AG/g plant). Additionally, we performed the isolation of a 9-epi-cucurbitane derivative and α-curcumene. Antimicrobial, anesthetic and antiinflammatory activities of the triterpene have been analyzed. This constituent was inactive at the tested concentrations. In the antimicrobial evaluation of the α-curcumene, this substance was active against S. aureus ATCC 25293, B. subtilis ATCC 6633, Escherichia coli ATCC 2792, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 44773 and Saccharomyces cerevisiae ATCC 28952. By the disk diffusion method, α-curcumene showed the occurrence of sensitizing bacteria to imipenem against E. cloacae with a significance level of 5%.